Isolasi Senyawa Metabolit Sekunder dari Ekstrak Etil Asetat Daun Sungkai (Peronema canescens jack.) dan Uji Aktivitas Imunomodulator - Safitri, Wulan; Latief, Madyawati; Susanto, Nindita Clourisa Amaris (Jambura Journal of Chemistry, 2024)
Sungkai (Peronema canescens Jack.) is a plant native to Indonesia that is traditionally used for dehumidifiers, treating malaria and increasing endurance. This study aims to isolate the compounds in the ethyl acetate extract of sungkai leaves and test the immunomodulatory activity of these compounds. Sungkai leaves were carried out stratified maceration using n-hexane, ethyl acetate and methanol solvents, then phytochemical screening of ethyl acetate extract of sungkai leaves, followed by an isolation process using the KVC method and isolates were obtained on F3. Phytochemical screening of F3 isolates contains steroid compounds. Immunomodulatory activity tests showed that in EEADS 50 mg/Kgbb, 150 mg/Kgbb, 450 mg/Kgbb, K+ and isolates there was an increase in the number of leukocytes and % macrophage activity compared to K-. The EEADS treatment of 50 mg/Kgbb, 150 mg/Kgbb and isolates of 0.7 mg/Kgbb did not differ markedly from K- but differed markedly from the EEADS treatment of 450 mg/Kgbb and K+. At a dose of 450 mg/Kgbb there was an increase in leukocytes and the highest % macrophage activity which was almost close to K+ (Imboost 0.7 mg/Kgbb). The UV-Vis spectrum of the F3 isolate shows a maximum absorption peak at 267 nm indicating the presence of a nonconjugation double bond. The FTIR spectrum shows isolates have groups O-H (3381.13cm-1), aliphatic C-H (2939.10cm-1), C=C (1631.44cm-1), C-H (1449.42-1362.82cm-1), and C-O (1022.32cm-1). Based on the literature comparison, the pattern of the UV-Vis spectrum and FTIR of F3 isolates has similarities with the UV-Vis and FTIR spectrum of steroid group compounds, namely Î²-Sitosterol.